Influencia de la arquitectura de México en la de España - Nafarrate Mexía, Enrique, 1930- (Editorial Conexión Gráfica, 1996)
"A brief but thought-provoking study of the reverse influence of Mexican architecture on that of Spain's during the colonial era. For example, the author says that the characteristic organization of prehispanic religious centers around large plazas, as seen at Palenque, Teotihuacan, and Chichenitza, was transferred first to Mexican and then to Spanish architecture. Also identifies Americanized architectural elements and decorative motifs in buildings in Murcia, Olivia, and in the Canary Islands. Contains a few photographs with drawings of mostly architectural details"--Handbook of Latin American Studies, v. 58.